2015
DOI: 10.1182/blood-2014-09-599159
|View full text |Cite
|
Sign up to set email alerts
|

CD24hiCD27+ and plasmablast-like regulatory B cells in human chronic graft-versus-host disease

Abstract: Key Points• Chronic graft-versus-host disease is associated with a global Breg defect.• This defect is particularly accentuated in the CD24 hi CD27 1 Breg compartment.Interleukin 10 (IL-10)-producing B cells (regulatory B cells [Bregs]) regulate autoimmunity in mice and humans, and a regulatory role of IL-10-producing plasma cells has been described in mice. Dysfunction of B cells that maintain homeostasis may play a role in the pathogenesis of chronic graft-versus-host disease (cGVHD) after allogeneic stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 63 publications
(96 reference statements)
5
119
1
4
Order By: Relevance
“…Alternatively, supranormal B-cell populations may also contain a significant component of regulatory B cells that promote immune tolerance through different mechanisms. 42,43 Although the etiology of delayed B-cell recovery in cGVHD remains an area of active investigation, these data support the critical role of bone marrow lymphogenesis and output for the maintenance of B-cell homeostasis and immune tolerance.…”
Section: Establishing B-cell Tolerance After Allogeneic Hsctmentioning
confidence: 92%
“…Alternatively, supranormal B-cell populations may also contain a significant component of regulatory B cells that promote immune tolerance through different mechanisms. 42,43 Although the etiology of delayed B-cell recovery in cGVHD remains an area of active investigation, these data support the critical role of bone marrow lymphogenesis and output for the maintenance of B-cell homeostasis and immune tolerance.…”
Section: Establishing B-cell Tolerance After Allogeneic Hsctmentioning
confidence: 92%
“…[4][5][6] Both murine models and clinical studies have shown that cGVHD is associated with multiple abnormalities of B-cell reconstitution including decreased numbers of B-cell progenitors, increased representation of memory B cells, and decreased frequency of regulatory B cells. 4,[7][8][9][10][11] cGVHD is also associated with high levels of B-cell activating factor (BAFF), high BAFF-to-B-cell ratios and aberrant B-cell activation. 4,6,10,12,13 The frequent detection of auto-and alloantibodies after HSCT and the clinical benefit of B-cell-targeted therapy also emphasize the important role of B cells in the development of cGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Reduction of interleukin-10 (IL-10)-producing regulatory B cells was found in cGVHD patients and murine models. [12][13][14] We reported that donor B cells augmented clonal expansion of pathogenic CD4…”
Section: Introductionmentioning
confidence: 99%